Development of Arabic comics as a learning media for reading skills at Sumenep State Islamic High School - Mufidha, Ulfatul; Sari, Risna Rianti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The purpose of this study was to determine the process of developing comics as a medium for learning maharah qiro'ah, and to test the effectiveness of comics as a medium for learning maharah qiro'ah in class XI of Madrasah Aliyah Negeri Sumenep. This study is a research and development (Research and Development) using the 4D model, which includes four stages: define, design, development, and disseminate. The data sources in this study were students of class XI and one Arabic language subject teacher. The results of this study are learning media in the form of Arabic comics that have been validated showing that: validation from material experts got a score of 100% in the